Parabolas And Circles.

Level pending

The parabola y = x 2 + 4 y = x^2 + 4 is tangent to a circle with radius 1 1 at points P P and Q Q as shown above.

If the area A A can be represented as A = a a b π a A = \dfrac{a\sqrt{a}}{b} - \dfrac{\pi}{a} , where a a and b b are coprime positive integers, find a + b a + b .


The answer is 7.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Rocco Dalto
Dec 8, 2019

D = r 2 = x 2 + ( x 2 + 4 y 0 ) 2 d D d x = 2 x ( 2 x 2 + 9 2 y 0 ) = 0 D = r^2 = x^2 + (x^2 + 4 - y_{0})^2 \implies \dfrac{dD}{dx} = 2x(2x^2 + 9 - 2y_{0}) = 0

x = 0 , x = ± 2 y 0 9 2 \implies x = 0, x = \pm\sqrt{\dfrac{2y_{0} - 9}{2}} and x 0 x = ± 2 y 0 9 2 x \neq 0 \implies x = \pm\sqrt{\dfrac{2y_{0} - 9}{2}} \implies

y 0 = 21 4 x = ± 3 2 y = 19 4 y_{0} = \dfrac{21}{4} \implies x = \pm\dfrac{\sqrt{3}}{2} \implies y = \dfrac{19}{4} .

Circle: y 2 ( x ) = 1 x 2 + 21 4 y_{2}(x) = -\sqrt{1 - x^2} + \dfrac{21}{4}

Parabola: y 1 ( x ) = x 2 + 4 y_{1}(x) = x^2 + 4

A R = 2 0 3 2 y 2 ( x ) y 1 ( x ) d x \implies A_{R} = 2\displaystyle\int_{0}^{\dfrac{\sqrt{3}}{2}} y_{2}(x) - y_{1}(x) dx = 2 0 3 2 ( 1 x 2 + 5 4 x 2 ) d x = 2\displaystyle\int_{0}^{\dfrac{\sqrt{3}}{2}} (-\sqrt{1 - x^2} + \dfrac{5}{4} - x^2) dx

Let x = sin ( θ ) d x = cos ( θ ) d θ x = \sin(\theta) \implies dx = \cos(\theta) d\theta \implies

A R = 2 ( 1 2 0 π 3 ( 1 + cos ( 2 θ ) ) d θ + 3 2 ) A_{R} = 2(-\dfrac{1}{2}\displaystyle\int_{0}^{\dfrac{\pi}{3}} (1 + \cos(2\theta)) d\theta +\dfrac{\sqrt{3}}{2})

= 2 ( 1 2 ( θ + 1 2 sin ( 2 θ ) ) 0 π 3 + 3 2 ) = 2(-\dfrac{1}{2}(\theta + \dfrac{1}{2}\sin(2\theta))|_{0}^{\frac{\pi}{3}} +\dfrac{\sqrt{3}}{2}) = 2 ( 1 2 ( π 3 + 3 4 ) + 3 2 ) = = 2(-\dfrac{1}{2}(\dfrac{\pi}{3} + \dfrac{\sqrt{3}}{4}) + \dfrac{\sqrt{3}}{2}) =

3 3 4 π 3 = a a b π a \dfrac{3\sqrt{3}}{4} - \dfrac{\pi}{3} = \dfrac{a\sqrt{a}}{b} - \dfrac{\pi}{a} \implies a + b = 7 a + b = \boxed{7} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...